Work Stress and Job Satisfaction Among Female Bankers in Nepal - Rayamajhi Sushma (Journal of Corporate Finance Management and Banking System, 2024)
The purpose of the study is to identify the causes of stress and how stress affects job satisfaction in the banking sector. Data on the employees' Satisfaction and stress levels are also provided by this study .Non-probability sampling was utilized to create a representative sample for the study, which included 16 different banks . There were 386 responders in the sample. A questionnaire was used to get the primary data from the respondents. One-way ANOVA, correlation, and regression analysis. The results of the study demonstrate that work-life balance, peer support, and stress connected to the job all significantly affect how well employees perform in the banking sector. The study also comes to the conclusion that employee happiness is not significantly impacted by organizational stress factors.